Investigation of the scanning performance and enhancement of an electrically large array - Cavanagh, Martin N. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2008.